Implementation of Anti-Usury Practices in Islamic Finance: A Case Study at PT. Kredit Tanpa Usury (KRTABA) East Lombok: Penerapan Praktik Anti Riba Dalam Keuangan Islam: Studi Kasus Di PT. Kredit Tanpa Riba (KRTABA) Lombok Timur - Hilalludin Hilalludin; Laily Alfi Zaitun Nisa (Journal of Islamic Economics, 2025)
This study aims to analyze the implementation of anti-usury principles in the financing practices of PT. Kredit Tanpa Riba (KRTABA), an Islamic financial institution operating in East Lombok Regency. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, direct observation, documentation, and literature review. Key informants include management, staff, customers, and Islamic economic scholars. The main focus of the study is to evaluate whether KRTABA’s financing practices are genuinely free from usury elements and aligned with Islamic principles, particularly regarding murabahah contracts, price transparency, and interest-free policies. The results show that KRTABA consistently avoids usury in all aspects of its operations. The institution applies fixed pricing without additional interest, eliminates down payments, and offers free services without hidden fees. All contracts are based on principles of fairness, honesty, and mutual assistance. The financing concept has had a positive impact on society by enhancing Islamic financial literacy and providing an alternative solution to the dominance of the conventional interest-based system. Therefore, KRTABA can be regarded as a model of inclusive, just, and practical Islamic financing institutions.